Efficient Route for the Synthesis of Diverse Heteroannelated 5-Cyanopyridines - Mityuk, Andrey P.; Hrebonkin, Andrii; Lebed, Pavlo S.; Grabchuk, Galyna P.; Volochnyuk, Dmitriy M.; Ryabukhin, Sergey V. (Synthesis, 2021)
The new efficient, convenient protocol for the synthesis of heteroannelated 3-cyanopyridines and pyrimidines starting from diverse aminoheterocycles and 3,3-dimethoxy-2-formylpropionitrile sodium salt was elaborated. The advantages and improvements of the procedure compared to previously known methods are shown. The scope and limitations of the method are determined. The impact of the structural features on regioselectivity are discussed. The preparativeness, scalability, and application scope of the elaborated protocol are demonstrated by the synthesis of five heteroannelated 3-cyanopyridines in quantities up to 100 grams.
Keywords: aminoheterocycles; heterocyclization; heteroannelated 3-cyanopyridines; heteroannelated 3-cyanopyrimidines; 2-dimethoxy-3-hydroxyacrylonitrile